Fragmenting Cybersecurity Norms Through the Language(s) of Subalternity: India in “the East” and the Global Community - Segate, Riccardo Vecellio (Columbia Journal of Asian Law, 2019)
The global cybersecurity discourse has never proved more fragmented than in the aftermath of the failure of the last United Nations Group of Governmental Experts on Developments in the Field of Information and Telecommunications in the Context of International Security. This discourse stands trapped in long-lasting and seemingly crystallized normative stances between “the West” and “the East,” yet it also calls upon the international community to regulate a wide spectrum of phenomena, ranging from thefts of digitally-stored trade secrets to large-scale pervasive attacks, which may soon reach the threshold of armed attacks. If one situates the major cybersecurity players on a sliding scale between freedom and control over cyber content and infrastructure, the mainstream stance would place the United States, the European Union, the United Kingdom, Brazil, India, China, and Russia in that order. Nonetheless, this scale is in practice more complex, in part due to the influence of the Shanghai Cooperation Organisation, a regional security forum which has witnessed major rebalancing after the membership expansion in June 2017. This paper scrutinizes India’s contribution towards a possible fragmentation of the “Eastern” cybersecurity discourse based on hard laws and state assertiveness, and the consequent disruption of the constructivist East-West binary dialectic about cyberwarfare, cyberterrorism, cyber espionage, and online data protection. By simultaneously negotiating its sub-alterity and rejecting its subalternity, India holds the potential to reshape an otherwise almost-coherent “cyber East.”